Crystal structure of dimethyl-bis(4-bromophenyl-κC 1)tin(IV), C14H14Br2Sn - Lee, See Mun *; Lo, Kong Mun *; Tiekink, Edward R. T. * (De Gruyter Open, 2021)
C14H14Br2Sn, monoclinic, P21/c (no. 14), a = 12.9848(2) Å, b = 18.9911(2) Å, c = 6.0550(1) Å, β = 99.136(1)°, V = 1474.19(4) Å3, Z= 4, Rgt(F) = 0.0193, wRref (F2) = 0.0490,T = 100 K.